Making the evidence (and arguments) count - Dunn, Michael (Journal of medical ethics, 2015)
The academic field of medical ethics continues to evolve. One of the starkest features of this ongoing evolution is the increase in research studies that incorporate an empirical component. Although this trend is not new (Borry et al., 2006),1 empirical papers in the Journal of Medical Ethics now constitute a significant contribution to each and every issue.Disciplinary turf wars were a feature of the early days of this ‘empirical turn’ in medical ethics as philosophers and social scientists sought to articulate and defend why their different contributions were necessary to the advancement of the field. Crudely characterised, these battles were pitched over philosophers' perceptions that social scientists lack rigour in articulating how the study of ethical attitudes and practices could inform normative reasoning, and by social scientists' perceptions that philosophers' analyses were blind to salient features of the real-world settings in which moral problems arise in health care practice and policy-making.As empirical contributions to medical ethics have expanded, these debates and disagreements have also evolved. One relatively new feature of the medical ethics and bioethics literature is the tendency to contrast ‘analytical’ medical ethics with ‘empirical’ medical ethics, as another of the journal's Associate Editors does in a recent piece in this column (Wilkinson, 2014).2 This distinction has some advantages. It can help to avoid some of the cheap shots that were a feature of the earlier disciplinary disagreements. In particular, differentiating medical ethics research in terms of its methodological orientation can help to avoid common misrepresentations of the contributions of different scholars, and it explicitly recognises that both theoretical and empirical contributions have merit in advancing the field.There are, however, problems with dividing up academic medical ethics in this way. One concern is the risk that, as the field matures, it will bifurcate …